Strategi Internal Relations Meningkatkan Loyalitas Dan Motivasi Kinerja Karyawan Hotel Sofia Juanda Surabaya - Angga Wahyu Perdana; Ratna Puspita Sari (LPPM Stikosa-AWS, 2022)
Hotel Sofia Juanda is company in the service industry which successful in keeping and saving employee loyalty. The research aims to find out the internal relations strategy used at the Hotel Sofia Juanda to increase loyalty and employee motivation. This research use qualitative descriptive method. All primary data obtained interviews and observation. Then a secondary data is documenations, obtained relates to research topics. Research has shown Hotel Sofia Juanda use element in the work loyalty factor, which make employee loyal to the company. Like rational factors, emotional factors, and spiritual factors. It's what makes this whole aspect of company loyalty possible, Like obeying the company rules, responsibility, and The spirit of work.